The Fed’s Monetary Policy Decisions and Stock Market Uncertainty : Evidence from years 2008 - 2022 - Virkajärvi, Jussi Jesper (My University, 2022)
In the 2020s financial markets have faced unseen wavering due the breakout of Covid-pandemic which eventually led into massive easing-programs from central banks. The Central bank of United States, The Federal Reserve, decisions have significant impact on stock markets, and the uncertainty related on the stock markets, through monetary policy decisions. In this study, I examine the Federal Open Market Committees, FOMC, decisions impacts on the volatility index VIX which is measured from the S&P 500 index on the announcement date of FOMC monetary policy decisions. Additionally, to previous studies, this study also examines whether the introduction of the press conference after FOMC announcement have an impact on the implied volatility. The sample period used in this study includes the years 2008 – 2022 and during sample period 125 FOMC meetings were held. Out of these meetings 117 were scheduled meetings and 8 were unscheduled meetings. The sample period includes 3707 daily quotes in the volatility index VIX. This thesis is following the study of Vähämaa and Äijö (2011) in which they studied the impact of FOMC monetary policy decisions on the uncertainty of stock markets. Both the result of their study and many other studies indicates that the volatility index VIX tends to decrease after FOMC monetary policy announcement, but previous literature also suggest that surprises related to monetary policy tend to increase the VIX index. The increase is driven by the surprises in the unscheduled meeting monetary policy announcements. (Chen & Clements, 2007a; Gospodinov & Jamali, 2015; Kurov, 2010; Nikkinen & Sahlström, 2004). Ordinary least square (OLS)- regression analysis indicates that the impact of FOMC monetary policy announcement is decreasing the volatility index VIX, which supports the findings from previous studies. The volatility measured from the S&P 500 tends to decrease after meetings and this finding is also statistically significant. Unlike many previous studies, this thesis is unable to identify statistically significant correlation between monetary policy surprises and implied volatility on FOMC announcement days. There were no significant correlations when examining the impact of the press conference, which indicates that it doesn’t play a significant role in stock market uncertainty. Widening the sample period and measuring the element of surprise with different methods is something that should be considered in future studies.

2020-luvulla rahoitusmarkkinat ovat kokeneet ennennäkemätöntä heiluntaa Covid-pandemian puhkeamisen johdettua lopulta massiivisiin elvytystoimiin keskuspankkien toi-mesta. Yhdysvaltojen keskuspankin The Federal Reserven rahapoliittisilla päätöksillä on mer-kittävä vaikutus rahoitusolosuhteiden kautta osakemarkkinoihin ja osakemarkkinoihin liitty-vään epävarmuuteen. Tässä tutkimuksessa tarkastellaan Fedin rahapolitiikasta päättävän arvomarkkinakomitean (Federal Open Market Committee, FOMC) rahapoliittisten päätösten vaikutuksia S&P 500 indeksistä johdettuun volatiliteetti-indeksi VIX:n muutoksiin arvomarkki-na-komitean päätösten julkistuspäivänä. Lisäksi tässä tutkimuksessa tutkitaan FOMC:n vuon-na 2011 esitellyn lehdistötilaisuuden vaikutusta volatiliteettiin. Tässä tutkimuksessa käytetään aineistoa vuosilta 2008–2022 ja tutkimusajanjakson aikana FOMC on kokoontunut yhteensä 125 kertaa. Näistä kokoontumisista 117 on ollut kalenterin-mukaisia suunniteltuja kokoontumisia ja 8 kokousta on ollut kalanteroimattomia. Lisäksi ai-neisto käsittelee 3707 volatiliteetti-indeksi VIX:n päätösarvoa. Tutkimus perustuu pitkälti Vähämaan & Äijön (2011) tekemään tutkimukseen, jossa he tutkivat Fedin rahapoliittisten päätösten vaikutusta osakemarkkinoihin liittyvään odotettuun epävarmuuteen. Sekä heidän, että muiden aiheeseen liittyvien tutkimusten tulokset osoittavat, että osakemarkkinoiden volatiliteetti laskee arvomarkkinakomitean kokousten jälkeen, mutta yllättävät rahapoliittiset päätökset, esimerkiksi odotettua suurempia koronnosto, vaikuttaa VIX-indeksiin nostavasti. Tutkimukset osoittavat, että ennen kaikkea ennakkoon suunnittelemattomiin kokouksiin liittyvät yllättävät rahapoliittiset päätökset nostavat odotettua volatiliteettia merkittävästi. (Chen & Clements, 2007a; Gospodinov & Jamali, 2015; Kurov, 2010; Nikkinen & Sahlström, 2004). OLS-regressioanalyysi osoittaa, että arvomarkkinakomiteon päätöksenteon vaikutukset ovat linjassa aikaisempien tutkimustulosten kanssa. S&p 500 indeksistä mitattu volatiliteetti laskee tilastollisesti merkittävästi arvomarkkinakomiteon päätöksenteon jälkeen. Päätöksentekoon liittyvien yllätysten merkitystä ei voitu arvioida merkittävin tuloksin eikä lehdistötilaisuuden vaikutuksista saatu merkittäviä tuloksia. Voidaan siis todeta, että päätöksenteko rauhoittaa osakemarkkinoita eikä lehdistötilaisuudella ole ollut merkittävää vaikutusta osakemarkkinoiden epävarmuuteen. Tarkempien tutkimustulosten saamiseksi, tutkimusaineistoa tulisi laajentaa entistä suuremmaksi ja tutkimuksen vaikutuksia pidemmän aikavälin epävarmuuteentutkia tarkemmin useammalla eri tavalla mitatulla yllätyskomponentilla
Keywords: volatiliteetti; keskuspankit; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance